Radiolabelled Polymeric Materials for Imaging and Treatment of Cancer: Quo Vadis?. Issue 6 (20th February 2017) - Pant, Kritee; Sedláček, Ondřej; Nadar, Robin A.; Hrubý, Martin; Stephan, Holger
Abstract : Owing to their tunable blood circulation time and suitable plasma stability, polymer‐based nanomaterials hold a great potential for designing and utilising multifunctional nanocarriers for efficient imaging and effective treatment of cancer. When tagged with appropriate radionuclides, they may allow for specific detection (diagnosis) as well as the destruction of tumours (therapy) or even customization of materials, aiming to both diagnosis and therapy (theranostic approach). This review provides an overview of recent developments of radiolabelled polymeric nanomaterials (natural and synthetic polymers) for molecular imaging of cancer, specifically, applying nuclear techniques such as positron emission tomography (PET) and single‐photon emission computed tomography (SPECT). Different approaches to radiolabel polymers are evaluated from the methodical radiochemical point of view. This includes new bifunctional chelating agents (BFCAs) for radiometals as well as novel labelling methods. Special emphasis is given to eligible strategies employed to evade the mononuclear phagocytic system (MPS) in view of efficient targeting. The discussion encompasses promising strategies currently employed as well as emerging possibilities in radionuclide‐based cancer therapy. Key issues involved in the clinical translation of radiolabelled polymers and future scopes of this intriguing research field are also discussed. Abstract : In this review the historical progress as well as recent advances of radiolabelled natural and synthetic polymers applied in cancer imaging and treatment, including drug delivery systems, are highlighted. Advantages and disadvantages of different radiolabelling as well as targeting strategies are discussed.